Developing science and technology - Damásio, Bruno (2023)
Damásio, B., Mendonça, S., & Silva, E. M. E. (2023). Developing science and technology: the role of Big Tech. In 32nd European Conference of the International Telecommunications Society (ITS): "Realising the digital decade in the European Union – Easier said than done?", Madrid, Spain, 19th - 20th June 2023 (pp. 1-42). International Telecommunications Society (ITS). https://www.econstor.eu/handle/10419/277951